PENGARUH KHLORHEKSIDIN DIGLUKONAT 2% DAN GLISERIN SEBAGAI BAHAN PENCAMPUR KALSIUM HIDROKSIDA TERHADAP SISA KALSIUM HIDROKSIDA PADA SEPERTIGA APIKAL DINDING SALURAN AKAR GIGI - Emmawati Prawitasari, Diatri Nari Ratih, dan Widowati Siswomihardjo (Jurnal Teknosains, 2013)
The most widely used intracanal medicament is calcium hydroxide (Ca(OH2). However, the residue ofCa(OH)2 in the root canal must be removed prior to obturation. The residue of Ca(OH)2 in the root canalwalls would result in apical leakage. This is due to the unstable dimension of Ca(OH)2, reduced flowand working time of the sealers, and decreased adhesion of sealers and gutta percha to root canal walls.This study aimed to determine the effect of Ca(OH)2 vehicles and agitation irrigation techniques on theresidue of Ca(OH)2 in the apical third of the root canal walls.Twelve extracted mandibular first premolars were used in this study. The crowns of the teethwere removed at the apical part of cemento enamel junction with a length of 14 mm from the apical.The canals were prepared with a Step Back technique to obtain Master Apical File ( MAF ) # 40. Thespecimens were randomly devided into groups I, the pastes of Ca(OH)2+chlorhexidine digluconate 2%.In groups II, the pastes of Ca (OH)2+ glycerin were applied. Each specimen of the study was sectionedin the sagittal direction, then was photographed under a stereo microscope at 120x magnification. Thepercentages of Ca(OH)2 residue were calculated using UTHSCSA image tool 3 software. Data wereanalyzed using T-test at 95% level of significance.The results revealed that the group of Ca(OH)2+ chlorhexidine digluconate 2% paste showed thelowest number of residual Ca(OH)2.The conclusion of this study was that the vehicles affected the totalresidue of Ca(OH)2.